The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2319/083020-756.1
|View full text |Cite
|
Sign up to set email alerts
|

Stability and success rate of dual-thread miniscrews:

Abstract: Objectives To date, the clinical stability of dual-thread orthodontic miniscrews has not been studied. This study aimed to compare the primary stability and long-term clinical success rate of dual-thread and cylindrical orthodontic miniscrews and to examine the association between various clinical factors and the success rate of miniscrews. Materials and Methods A total of 145 cylindrical and 135 dual-thread miniscrews were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The affection of sex was also found to be controversial. While some studies reported that there were no statistical differences [ 58 60 , 65 ], others reported that males had a higher success rate due to higher bone density [ 59 , 62 ].…”
Section: Complications Under Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The affection of sex was also found to be controversial. While some studies reported that there were no statistical differences [ 58 60 , 65 ], others reported that males had a higher success rate due to higher bone density [ 59 , 62 ].…”
Section: Complications Under Loadingmentioning
confidence: 99%
“…Among risk factors from patients, the association between miniscrew failure and age was not consistent. Some studies showed no relationship between age and failure [58][59][60]; whereas others found that age could affect the miniscrew stability since there was poorer quality and higher bone turnover rate in growing patients compared to adults, affecting optimal mechanical miniscrew stability in adolescents [61][62][63][64][65]. Therefore, more attention should be taken to the miniscrew placement in younger patients.…”
Section: Complications Under Loadingmentioning
confidence: 99%
“…In addition, the anchorage on micro‐implants prevents unwanted movements of tooth elements that were used in conventional orthodontic steps. Thus, offering an alternative optimal solution to orthognathic surgery in cases where dental anchorage may result in undesirable adverse effects such as vertical dimension changes produced by the use of conventional inter‐maxillary forces 2 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is believed that primary stability is essential for the success of mini‐screws 2,3 . Risk factors for the stability of mini‐screws can be divided into four categories: host‐related risks (age, sex, oral hygiene, cortical bone thickness, root proximity, and the location of the insertion ‘maxilla or mandible’, mini‐screw‐related risks (shape, diameter, and length of the screws), surgical management‐related risks (insertion torque, angle, placement height in the movable mucosa or attached gingiva, need for pre–drilling) 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study used tapered, self-tapping, ϕ2.0 × 6 mm OASs, and reported ITs of 25.6 ± 5.5 Ncm [8], whereas another study used cylindrical, self-drilling, ϕ1.5 × 7 mm OASs in the maxillary buccal alveolar area and reported ITs of 6.0 ± 3.2 Ncm [9]. Thus, the IT values vary greatly with the placement method and OAS design (screw diameter, length, and tapered or cylindrical form) [1,[5][6][7][8][9][10][11][12][13][14][15]. Therefore, clinicians may be hesitant to apply these values in practice.…”
Section: Introductionmentioning
confidence: 99%